2019
DOI: 10.1108/bfj-02-2019-0140
|View full text |Cite
|
Sign up to set email alerts
|

Customer loyalty in the fast food restaurants of Bangladesh

Abstract: Purpose The purpose of this paper is to investigate the factors influencing the satisfaction of customer and customer loyalty in the fast food restaurant industry. A theoretical model, including hypotheses, has been proposed in this study. Design/methodology/approach Data were assembled using convenient sampling method. The hypothesized model was verified with the data from 204 respondents. Principal component analysis and structural equation modeling approach were applied to analyze data. Findings The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
89
1
26

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(131 citation statements)
references
References 50 publications
(53 reference statements)
15
89
1
26
Order By: Relevance
“…In recent years, the global fast-food industry has seen enormous growth [1]. The trend is equally observed in developing countries [2], and Pakistan is not an exception to that. The fast-food industry is one of the most rapidly growing sectors (2nd largest industry in Pakistan), employing 16% of the manufacturing labor force and feeding 180 million consumers.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the global fast-food industry has seen enormous growth [1]. The trend is equally observed in developing countries [2], and Pakistan is not an exception to that. The fast-food industry is one of the most rapidly growing sectors (2nd largest industry in Pakistan), employing 16% of the manufacturing labor force and feeding 180 million consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Rasa menjadi salah satu aspek yang diperhitungkan dalam kualitas minuman. Dalam penelitian sebelumnya, rasa menjadi variabel yang paling berpengaruh terhadap kepuasan pelanggan coffee shop dan juga restoran (Arinda et al, 2018;Belal, 2019;W. S. Lee et al, 2018).…”
Section: Atribut Terkait Kepuasan Pelanggan Dan Pengembangan Hipotesisunclassified
“…Enam variabel berupa suasana, sikap karyawan, layanan IT, kualitas minuman, citra merek dan variasi menu merupakan variabel-variabel yang mempengaruhi kepuasan pelanggan, dimana kepuasan pelanggan tersebut pada akhirnya juga akan mempengaruhi loyalitas merek. Beberapa penelitian digunakan sebagai referensi alat pengukuran dalam penelitian ini, antara lain: suasana (Grayson & McNeill, 2009;Heide et al, 2009; W. S. Lee et al, 2018;Parsons, 2011), sikap karyawan (Adsit et al, 1996;Bodderas et al, 2011;Eccles & Durand, 1997; W. S. Lee et al, 2018), layanan IT (Bulchand-Gidumal et al, 2011;Jeon et al, 2019;Kim, 2010; W. S. Lee et al, 2018), kualitas minuman (Arinda et al, 2018;Belal, 2019; W. S. Lee et al, 2018;Matzler et al, 1996), citra merek (Arinda et al, 2018;Martínez et al, 2014;Ogba & Tan, 2009), variasi menu (Arinda et al, 2018;Beldona et al, 2014;Lindholm et al, 2018), kepuasan (Arinda et al, 2018; W. S. Lee et al, 2018;Matzler et al, 1996), loyalitas (Arinda et al, 2018; W. S. Lee et al, 2018).…”
Section: Metode Penelitianunclassified
“…Many factors were identified to influence customer satisfaction when visiting food premises, including, food taste, service, price, environment and hygiene [ 3 , 4 ]. A study conducted by Fatimah and colleagues (2011) on Malaysian customers found that cleanliness was the main factor followed by food variety and location of the premises as criteria in selecting dining places [ 5 ].…”
Section: Introductionmentioning
confidence: 99%